2019
DOI: 10.2106/jbjs.rvw.19.00055
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) and Their Effect on Musculoskeletal Soft-Tissue Healing

Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are being increasingly employed as a part of multimodal non-opioid strategies to treat postoperative pain. In the present study, we sought to review the effects of short-term NSAID use on musculoskeletal softtissue healing. Methods: We performed a scoping review of all studies that included the use of NSAIDs and their effect on healing of soft tissues, which for the purpose of this review refers to non-osseous musculoskeletal tissue such as ligament, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 56 publications
0
31
0
2
Order By: Relevance
“…A recent systematic review indeed demonstrated that the selective COX-2 inhibitors could negatively affect the healing process, though some other studies demonstrated no negative effect. 56 That's why cautions is needed for surgeons when administering NSAIDs/COX-2 inhibitors after ACL reconstruction, probably good to keep the duration and dosage of NSAIDs as short and low as possible to while avoiding unpleasant effect on the graft. 57 …”
Section: Histological and Biochemical Characterization Of Graft Healingmentioning
confidence: 99%
“…A recent systematic review indeed demonstrated that the selective COX-2 inhibitors could negatively affect the healing process, though some other studies demonstrated no negative effect. 56 That's why cautions is needed for surgeons when administering NSAIDs/COX-2 inhibitors after ACL reconstruction, probably good to keep the duration and dosage of NSAIDs as short and low as possible to while avoiding unpleasant effect on the graft. 57 …”
Section: Histological and Biochemical Characterization Of Graft Healingmentioning
confidence: 99%
“…NSAIDs inhibit prostaglandin synthesis by inactivation of cyclooxygenase-I (COX1) or COX2 enzymes. Prostaglandins produced by COX1 are involved in platelet aggregation, gastric mucosal integrity, and renal blood flow, while COX2 derived prostaglandins contribute to pain and inflammation ( FitzGerald, 2003 ; Ghosh et al, 2019 ). Therefore, the result of non-specific COX inhibition is decreased inflammation and analgesia but with non-desirable secondary effects.…”
Section: Clinical Evidence For Tendon Immunomodulation Therapiesmentioning
confidence: 99%
“…In rat models of Achilles tendon tear, post-operative treatment for 14 or 18 days with both indomethacin (COX1 and COX2 inhibition) and celecoxib (COX2 inhibition) improved tendon tensile strength ( Forslund et al, 2003 ). However, in a systematic review of randomized control trials in humans, selective COX2 inhibition was consistently associated with impaired tendon, labrum, and ligamentous healing, suggesting a requirement for inflammation in reparative healing ( Ghosh et al, 2019 ). While the role of COX2 related prostaglandins in tendon repair is unclear, timing appears to be a critical factor.…”
Section: Clinical Evidence For Tendon Immunomodulation Therapiesmentioning
confidence: 99%
“…Soft‐tissue wound healing follows the pattern of the four phases of haemostasis, inflammation, proliferation, and maturation/matrix remodelling 10 . There are many interfering factors, which will impede the progress of wound healing 11 . For the treatment of soft‐tissue injury, the wound is usually cleaned thoroughly and then covered with gauze directly.…”
Section: Discussionmentioning
confidence: 99%